Population diversity and genetics of Urochloa interspecific breeding populations - Perea, Claudia; Jauregui, Rosa (2025)
Here, we present a population genetics and structure analysis of the CIAT Urochloa interspecific breeding population based on over one million high-quality biallelic SNP markers mapped to the U. decumbens tetraploid reference genome. We characterize patterns of genetic diversity, inbreeding coefficients, allelic richness, and population structure across founders, sequential breeding cycles, and sexual recombination populations. Our analysis addresses key questions about breeding program effectiveness: How much of the founder genetic diversity has been retained? Are sexual populations successfully generating genetic variation? What is the population structure across species boundaries in this interspecific system? The insights generated inform broader strategies for maintaining genetic diversity in complex polyploid breeding systems.